Lipidic profile, dyslipidemia and physical exercises - Monique da Silva Gevaerd; Robert Oliveira da Cruz; Giuliano Mannrich; Michele de Souza; Lucieli Cambri (Universidade Federal de Santa Catarina, 2006)
The dyslipidemias are characterized by changes in the metabolism of lipids that leads to alterations in plasmatic lipoproteins concentrations representing a strong predictor of chronic-degenerative diseases. Epidemiologic studies show that there is also an inverse relationship between dyslipidemia and mortality indices of cardiovascular complications. Considering that physical activity offers numerous benefits on dyslipidemia prevention and treatment, the aim of this study was to make a review about lipoproteins, dyslipidemia, aerobic exercise, weight resisted exercises and their relationship. The literature search was based on PUBMED and LILACS databases, using the following keywords: lipoproteins, dyslipidemias, exercise, body composition, body fat. Thirty-six articles were selected giving priority to the most recent and original. The majority of publications reports the efficiency of aerobic exercises to improve the lipids profile. However, it is verified that studies with this specific objective are in greater number when compared with the weight resisted exercises. These studies affirm that the changes on the lipids profile induced by physical exercises happen through reduction of body mass and body fat accomplished by changes on fat distribution and enzymes that regulate the metabolism of lipoproteins. These changes can be observed in sedentary, physically active individuals or athletes. In spite of that, it was noticed that some statements in the literature as adequate volume and intensity are contradictory which indicates that more studies concerning lipoproteins and different exercise methods are necessary. RESUMO Dislipidemias são modificações no metabolismo dos lipídios que desencadeiam alterações nas concentrações das lipoproteínas plasmáticas, favorecendo o desenvolvimento de doenças crônico- degenerativas. Estudos epidemiológicos demonstram que as dislipidemias estão associadas às doenças cardiovasculares representando a principal causa de mortalidade entre adultos. Dentro deste contexto, enfatizando-se a prática de exercícios físicos como fator essencial na prevenção e tratamento das dislipidemias, o objetivo deste trabalho foi realizar uma revisão sobre a influência de exercícios aeróbios e exercícios resistidos com pesos no perfil lipídico e nas dislipidemias. Para a busca dos artigos foram consultadas as bases de dados PUBMED e LILACS, utilizando os termos: lipoproteins, dyslipidemias, exercise, body composition, body fat. Foram selecionados 36 artigos, entre os anos de 1993 e 2005, dando-se prioridade aos artigos originais mais recentes. Os dados desta revisão nos permitem concluir que, a maioria das publicações demonstram a eficiência dos exercícios aeróbios na melhora do perfil lipídico. No entanto, verifica-se que os estudos com este objetivo específico são em maior número quando comparado aos com exercícios resistidos com pesos. De maneira geral, as alterações no perfil lipídico induzidas pelos exercícios ocorrem através da redução da massa e da gordura corporal e de mudanças nadistribuição desta gordura e na atividade das enzimas que regulam o metabolismo das lipoproteínas. Estas alterações podem ser observadas em indivíduos sedentários, fisicamente ativos ou atletas. Entretanto, algumas questões, como volume e intensidades adequados, ainda são contraditórias sendo necessários mais estudos, envolvendo perfil lipídico e as diferentes formas de exercícios.